The Wiggles. Super Wiggles [videorecording (DVD)] - Field, Anthony, 1963-; Gillespie, Lachlan; Hawkins, Tsehay; Pryce, Simon (Wiggles, 2022)
Calling all superheroes! Join Anthony, Lachy, Simon, and Tsehay as they join forces with the "Fruit Salad TV" Wiggles Evie, Kelly, Caterina, and John, to celebrate the everyday heroes in our community. Featuring over 25 brand new songs, Super Wiggles showcases the newest members of Wiggle Town in catchy new tunes. Plus, we meet new friends such as the wonderful Super Granny; Super Ballet Man, Chengwu, who demonstrates his amazing dance skills; and the multi-talented Paloma the Mermaid. The Super Wiggles remind us that not all heroes wear capes and that superheroes are everywhere, from teachers to the lollipop person, to even the garbage truck driver. Who knows, you may even be one too!